Online Game Addiction and Gen Z: A Comparative Study on Turkish and Romanian High School Students - Huri Deniz Karcı; Bahar Urhan (Selçuk İletişim)
As being among “the digital natives” of the technology era, Generation Z and their online behaviors are important subjects to study in depth. Surrounded by technology, Generation Z is easily getting and using all technology products, and they do not feel any constraint about spending time with them, which might lead to a kind of addiction. The study was designed to examine the two-factor solution of online gaming addiction by Faraci and her colleagues’ internet addiction version employing the IAT of 20 items by Young. In order to reveal the present state, two field studies in two high schools from Turkey and Romania were run comparatively. Turkish and Romanian participants replied the 20-item-IAT and the questionnaire about online gaming behavior via an online survey platform. To determine the dimensions of online gaming addiction exploratory factor analysis and confirmatory factor analysis are performed. Reliability coefficients of both factors were satisfactory. According to confirmatory factor analysis goodness-of-fit indexes in both samples were reasonable. In conclusion, both factors fit well into the present study producing some other results about online gaming behavior, as well.